Early lymphocyte recovery after allogeneic transplantation of hematopoietic stem cells in patients with haematological malignancies: a single-centre experience - Kameliya Kostadinova; Krasen Venkov; Yonka Lazarova; Emilia Naseva; Ivan Tonev (Journal of Biomedical & Clinical Research)
Introduction: Allogeneic hematopoietic stem cell transplantation (AlloHSCT) is a therapeutic method for the treatment of many malignant and non-malignant hematological diseases but is still associated with significant morbidity and mortality. Disease relapse recurrence and non-relapse mortality (NRM) remain the main causes of failure from AlloHSCT. The identification of the risk factors associated with this continue to be a subject of extensive scientific research.Aim: The aim of our study was to identify the prognostic significance of the early lymphocyte recovery (ELR), presented as absolute lymphocyte count (ALC) for the outcome of AlloHSCT.Materials and methods: 96 patients with diagnoses of acute myeloid leukemia (AML), myelodysplastic syndrome (MDS) and acute lymphoblastic leukemia(ALL) who underwent AlloSCT at the Hematopoietic Stem Cell Transplantation Unit of SHATHD between 2017 and 2021 were included in the study. Based on our previous study on the prognostic role of ELR such as absolute lymphocyte count (ALC) on the outcome of AlloSCT, in terms of overall survival (OS), patients were divided and evaluated into two groups.Results: At a median follow-up of 54.7 months , median OS, progression-free survival (PFS), cumulative incidence of relapse (CIR), and NRM for patients with ELR were not reached. Disease risk index (DRI), response to AlloSCT and choice of haploidentical donor were identified as significant risk factors for ELR. Analysing the data regarding the significance of ELR in post-transplant complications led to important conclusions regarding aGvHD, cGvHD and associated survival.Conclusion: ELR is an established, clinically significant prognostic factor for transplant outcome. Identification and modelling of risk factors and complications associated with ELR can significantly improve outcomes of AlloSCT.